Thinking Outside the Box from The Perspective of a Malaysian School Administrator During A Pandemic as A New Educational Form - Nazeri Mohammad; Arshad Jais (Universitas Pendidikan Indonesia (UPI), 2023)
The purpose of this study was to describe Out of the Box from Malaysian School Administrators’ Perspective During Pandemic. We did a literature review to explain this matter. We believe that this study can be used as a reference for the education perspective.